Just water transitions in Egypt: civil society and equitable irrigation management - Eldabbagh, Fayrouz; Abdelwahab, Noura (American University in Cairo. Alternative Policy Solutions, 2025)
This policy paper examines pathways for achieving water justice in Egypt through equitable and efficient agricultural water management, focusing on the roles of civil society organizations (CSOs) and Water Users Associations (WUAs). Grounded in environmental justice literature and stakeholder consultations, the study defines water justice through two key dimensions: distributive justice, which entails fair access to water quantity, quality, and affordability while preventing overexploitation; and procedural justice, which emphasizes participatory policymaking channels for WUAs and CSOs. The analysis identifies six critical challenges: unequal water access (quantity and quality) in vulnerable regions, poor community water management, aging irrigation infrastructure and limited adoption of innovations, fragmented governance, inadequate law enforcement, and limited financing for irrigation improvements.